Challenges and inputs of the gender perspective to the study of vector borne diseases. - Luz Arenas-Monreal; Maricela Piña-Pozas; Héctor Gómez-Dantés (Instituto Nacional de Salud Pública, 2015)
The analysis of social determinants and gender within the health-disease-care process is an imperative to understand the variables that define the vulnerability of populations, their exposure risks, the determinants of their care, and the organization and participation in prevention and control programs. Ecohealth incorporates the study of the social determinants and gender perspectives because the emergency of dengue, malaria and Chagas disease are bound to unplanned urbanization, deficient sanitary infrastructure, and poor housing conditions. Gender emerges as an explanatory element of the roles played by men and women in the different scenarios (domestic, communitarian and social) that shape exposure risks to vectors and offer a better perspective of success for the prevention, control and care strategies. The objective is to contribute to the understanding on the gender perspective in the analysis of health risks through a conceptual framework.